Central adiposity increases the odds for plasma folate deficiency among Chinese women of reproductive age - Zhang, Jinjuan; Du, Yushan; Che, Xiaoyu; Xia, Shuangbo; Zhang, Le; Liu, Jufen (Frontiers in Public Health, 2022)
Objective To explore the association between adiposity and plasma folate deficiency odds among women of reproductive age in China. Methods A cross-sectional survey on nutritional status among women of reproductive aged 18–30 years in 2005–2006 in China was conducted. General adiposity was defined as body mass index (BMI) ≥24 kg/m2, and central adiposity was defined as waist circumference >80 cm. A plasma folate concentration <10.5 nmol/L (measured through microbiological assay) was defined as plasma folate deficiency. Odds ratios (ORs) and 95% confidence intervals (CIs) for plasma folate deficiency were calculated using a logistic regression model, with adjustment for potential confounders. Results A total of 3,076 women of reproductive age were included in the final analysis. Compared to women with normal BMI and WC, women with both general and central adiposity had the highest odds for plasma folate deficiency (OR = 3.107, 95% CI: 1.819–5.307). Women with exclusively central adiposity had excess odds for plasma folate deficiency (WC > 80 cm, BMI <24 kg/m2; OR = 2.448, 95% CI: 1.144–5.241), which was higher than women with exclusively general adiposity (BMI ≥ 24 kg/m2, WC ≤ 80 cm; OR = 1.709, 95% CI: 1.259–2.319). The combined use of BMI and WC can detect more women (11.7%) at higher plasma folate deficiency odds than either used alone. Conclusions Women with central adiposity in normal weight have higher odds for plasma folate deficiency than those with general obesity only. Early screening for central adiposity among women of reproductive age would be meaningful to prevent folate deficiency and improve life-cycle health.